PENDAMPINGAN USAHA LEMANG (TIMBU) KHAS DESA BOLO UNTUK MENINGKATKAN NILAI JUAL - M. Rimawan; Nur Khusnul Hamidah; Hanifah Muthiah; Ardiansyah (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
Abstract: The number of lemang entrepreneurs typical food of Bolo Village is decreasing even from lemang entrepreneurs who are still in production, their sales volume is decreasing. The main factors that cause this condition are low business management skills, no touch of technology, unattractive product displays, dirty and dusty, unhygienic, no labels and packaging so that it has an impact on reducing people's buying interest. Another problem faced by partners is that the production of lemang does not last long, as well as the low ability of partners to make jam as a complementary product from lemang. The activity methods used in community service activities include assistance in the form of changing mindsets regarding business management, training, and practice, as well as tool design as well as design/brand and packaging development. At each stage of the activity an evaluation is carried out both process evaluation and outcome evaluation so that the output of the activity can be measured. The results of this activity: 1) there is a change in mindset regarding business management; 2) the innovation of Lemang products; and 3) the existence of a label/brand design and product packaging